The influences of the experiential learning Tutoring Project on ELT pre-service teachers’ professional development = Ảnh hưởng của chương trình học trải nghiệm Tutoring Project đối với phát triển nghề nghiệp của sinh viên sư phạm tiếng Anh - Nguyễn, Phương Hà (2020)
Experiential learning has been widely employed in professional training, especially pre-service teachers’ training, as a supplementary to formal theoretical instruction. The purpose of experiential learning in pre-service teachers’ education is to put the theory into practice, thereby reinforcing knowledge acquisition. However, in this paper, the impact and purpose of experiential learning is re-examined in the light of the Tutoring project 2015 – 2016, where the preservice teachers prepared and conducted lessons in pairs or groups even though they did not receive any formal training in pedagogy before and during the project. The research investigated the influences of the experiential learning Tutoring project on pre-service teachers’ professional development from the aspects of challenges.